Performance Analysis Of Unit Trust In Malaysia - Chee, Khern Tuan (2003)
In this research, the performance of 138 Malaysian unit trust funds in the period of january 1990 to December 2002 is determined by using monthly net asset value and gross distributions. It includes an investigation into the aspects of return and risk characteristic, risk-adjusted performance, congruence of performance with fund objective, degree of risk diversification, consistency of performance and the influence of market proxies.